Communication strategies and collaboration of Malaysian ESL learners in oral interaction / Che Rushita @ Rushita Ismail - Ismail, Che Rushita @ Rushita (2012)
The study reported in this thesis is an analysis of the use of communication strategies and collaboration of Malaysian ESL learners in oral interaction. It examined how Malaysian ESL learners manage to communicate their message in second language face-to-face oral interaction when the intended target language lexical items or structures to express meaning are unavailable. More specifically, the study aimed to analyse how learners and interlocutors convey meaning through the use of communication strategies when the desired lexical items or structures are unavailable. It also analysed how communication was achieved through joint and collaborative efforts of the learners and interlocutors and the extent to which communication strategy use and collaborative efforts provided new lexical input for the learners. The study utilized a qualitative research design of a descriptive interpretative case study. Participants were 16 dyads of university students majoring in Applied Language Studies at Universiti Teknologi MARA Shah Alam working on a picture-story narration of spot-the-difference task. In this study, the dyads' usage of communication strategies and collaboration were analysed when they communicated the same set of pre-selected 32 referents. A stimulated recall interview was carried out at the end of the task through the replay of video recorded data. Comments made on the encountered linguistic difficulties and strategies they employed earlier in the task were audio recorded. The analysis of the data findings revealed that learners and interlocutors used communication strategies in singles or in combinations. Oral communication strategies also co-occurred with nonverbal communication strategies. Achievement communication strategies were used more than avoidance communication strategies when learners attempt to develop other means of expression to communicate the desired meaning as to compensate for the gap of the intended interlanguage item or structure. For communication of meaning to be successful, learners used communication strategies to present the information to be added to their and their interlocutors' shared common ground. Learners and interlocutors worked together to establish a mutual belief that the meaning uttered was understood through grounding procedures. Through collaborative efforts and joint actions of both interlocutors, Malaysian ESL learners collaborate to establish mutual belief and agreement on the meaning in the strategic communication. The use of communication strategies and collaboration among learners was seen to elicit cognitive processes that promote second language learning.